Pengaruh Kepercayaan dan Kepuasan Pelanggan pada Proses Bisnis E-commerce - Chairunnisa, Chairunnisa; Dewi, Siti Elis Puspita; Malakiyyah, Siti Nurhalifah (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to explain the exact relationship between trust and customer satisfaction in e-commerce business processes. This research is a type of qualitative research method with a literature review approach and collecting information that has been obtained from literature, online journal articles sourced from Google Scholar and reference books related to this article. The research results show that consumers will feel confident and decide to buy products through e-commerce platforms by considering several considerations and customer trust will continue to increase when using services, products and even recommending them to other people. Thus, it can be concluded that: 1) Satisfaction has a significant effect on e-commerce business processes. 2) Trust has a significant effect on e-commerce business processes.